B4C/SiC ceramic hollow microspheres prepared by slurry-coating and precursor conversion method. Issue 2 (February 2022) - Yan, Dexuan; Chen, Jiahui; Zhang, Yu; Gou, Yanzi
Graphical abstract: Highlights: B4 C/SiC ceramic hollow microspheres with high sphericity and smooth surface were fabricated. Aiming to enhance compatibility and dispersity of the slurry, the B4 C powder was grafted with polycarbosilane. Liquid polycarbosilane was added into slurry to eliminate cracks and smooth surface. Deoxidation was explored to remove oxygen from hollow microspheres and enhance hollow microspheres crush load. Abstract: In this work, a new approach to fabricate B4 C/SiC ceramic hollow microsphere was established through combination of slurry-coating and precursor conversion method. Firstly, different slurries were prepared using modified B4 C powder with addition of PCS and LPCS. Subsequently, slurry was coated on a POM microsphere, followed by crosslinking, POM decomposition and heat-treatment at 1100 °C. Finally, the B4 C/SiC hollow microspheres with average diameter of 1.6–1.9 mm and thickness of 10–60 μm were obtained. The roughness (Ra) of outer surface was as low as 40.3 nm with high sphericity of 99.6%. Deoxidation was also explored by heat treatment at 1700 °C. The oxygen content was decreased from 11.06 wt.% to 0.37 wt.%, and crush load was promoted from 1.73 N to 4.50 N. The preparative method of B4 C/SiC ceramic hollow microspheres in this work can be easily extended for large-scale production.